Multiscale hierarchical composite with extremely specific damping performance via bottom-up synergistic enhancement strategy - Haibo Feng; Chenhao Xu; Linghua Xiao; Li Li (Virtual and Physical Prototyping)
Existing hierarchical damping composites focus on either the intrinsic damping sources at the nanoscale or the damping excitation effect at the mesoscale, resulting in limited improvement in damping performance. This paper proposes a multiscale hierarchical synergistic strategy for damping enhancement and creates multiscale hierarchical composites with extremely specific damping performance. In addition to the traditional physical damping source at the nanoscale, a chemical damping source is introduced. Considering carbon nanotubes-induced features as the micro-hierarchy and skeleton lattices as the meso-hierarchy, the microstructure of the hard phase at each level of the composite material structure is designed to utilise both their rigidity-enhancing effect and the damping excitation effect by guiding the hard-phase-driven deformation mechanism. The multiscale hierarchical composite achieves a loss modulus of up to 1.54 GPa, surpassing the limited loss modulus of conventional engineering materials. This work offers a bottom-up design strategy and opens a transformational path toward high-performance composites.